New imaging tools reveal live cellular collagen secretion, fibril dynamics and network organisation - Olivia Kent; Eleanor R. Casey; Max Brown; Steven Bell; Matthew C. Ehrman; Michael J. Flagler; Arto Määttä; Adam M. Benham; Timothy J. Hawkins (Scientific Reports)
Abstract Although light microscopy has been used to examine the early trafficking of collagen within the cell, much of our understanding of the detailed organisation of cell deposited collagen is from static electron microscopy studies. To understand the dynamics of live cell collagen deposition and fibril organisation, we generated a bright photostable mNGCol1α2 fusion protein and employed a range of microscopy techniques to follow its intracellular transport and elucidate extracellular fibril formation. Our findings reveal the dynamics of fibril growth and the dynamic nature of collagen network interactions at the cellular level. Notably we observed molecular events that build network organisation, including fibril bundling, bifurcation, directionality along existing fibrils, and looping/intertwining behaviours. Strikingly, mNGCol1α2 fluorescence intensity maxima can mark a fibril before another growing collagen fibril intersects at this location. Real-time, high-resolution imaging of collagen has enabled fibrillogenesis and organisational dynamics to be visualised together in an actively secreting cellular system. We also show that the N-terminal protease site is not an absolute requirement for collagen fibril incorporation. This approach paves the way for assessing the dynamic organisation and assembly of collagen into the extracellular matrix in skin models and other tissues during health, ageing and disease.